Study and Analysis of the Performance of the Propulsion System of the K-61 Type Amphibious Vehicle for Artillery Transport (KAPA) - Good Rindo; Ahmad Fauzan Zakki; Farell Elghifari Putratama; Berlian Arswendo Adietya; Sapto Wiratno Satoto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
The application of waterjet propulsion systems in amphibious combat vehicles, such as the KAPA Type K-61 used by the Indonesian National Armed Forces (TNI) for transporting artillery munitions, is crucial for enhancing operational performance. The working principle of a waterjet involves drawing water from beneath the vehicle's hull, accelerating it through a pump, and expelling it to generate thrust. The design of the waterjet propulsion system significantly impacts the thrust produced. This study aims to evaluate the maximum performance achievable by the waterjet propulsion system of the KAPA Type K-61. The analysis is conducted using various Index Velocity Ratio (IVR) values, including IVR 0.28, which represents the current speed of the KAPA Type K-61, and other variations such as IVR 0.54, 0.59, 0.67, 0.70, 0.78, 0.94, 1.18, 1.64, and 2.38. The analysis results include the thrust value produced at the waterjet outlet, efficiency, and propulsion power. The study found that at an IVR of 2.38, the system produced the highest thrust of 30.72 N, with a propulsion power of 7315.13 Watts, equivalent to 9.95 Horsepower, and the highest efficiency of 99.21%. Based on the research conducted, it is recommended that future studies create a geometric model of the KAPA Type K-61 with original and more detailed dimensions and perform a 1:1 scale analysis to strengthen the obtained results. Additionally, analyzing the waterjet propulsion system along with the impeller or propeller system is also suggested to gain a more comprehensive understanding of the overall propulsion system's performance and efficiency.